The Efficacy of Intravenous Non-dextran Iron Sucrose in the Treatment of Iron-Deficiency Anemia in Pregnancy - Azra Arıcı Özkan; Muzaffer Sancı; Tahir Özgüder; Aysel Akgüner; Çiğdem İspahi (Medical Network, 2006)
OBJECTIVE: Iron-deficiency anemia is the most common type of anemia in pregnancy. In our study, the efficacy of non-dextran intravenous (IV) iron sucrose complex in the treatment of iron deficiency anemia of pregnancy is investigated. STUDY DESIGN: The study included 46 pregnant women who admitted to our hospital for routine antenatal follow-ups between January 2000 and June 2001 and had hemoglobin (Hb) value lower than 10gr/dl. Other ty pes of anemia were discarded after diagnostic examinations including Hb electophoresis applied in each case. The IV iron sucrose therapy lasted three weeks. The f irst week it was given on three days in increasing doses, making a total of 350 mg/week. On the following weeks, 400mg/week was given according to the patients Hb level. The patients were hospitalized on the first week in case of an anaphylactic reaction but on the following weeks it was applied in an outpatient basis. Cases were monitorized for Hb, hemotocrit, reticulocytosis, total iron binding capacity, serum iron and ferritin values. RESULTS: The mean age of the patients was 28±4.6 weeks. The Hb values increased at least by 0.8 gr/week in all cases. After the IV iron sucrose therapy, the most signif icant change was observed in the serum ferritin level (p<0.05). There were no side effects noted during the treatment. CONCLUSION: The treatment with non-dextran IV iron sucrose complex is a safe alternativ e with fast efficacy and low rate of side effects, decreasing the need for blood transfusions in pregnancy.